Science of Literature : The Field Day Anthology of Irish Writing, Volumes IV and V, and the Making of Irish Feminism - Sanches, Zuzanna (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
.